Broad‐Based Employee Stock Ownership: Motives and Outcomes - KIM, E. HAN; OUIMET, PAIGE (Journal of Finance, 2014)
ABSTRACT Firms initiating broad‐based employee share ownership plans often claim employee stock ownership plans (ESOPs) increase productivity by improving employee incentives. Do they? Small ESOPs comprising less than 5% of shares, granted by firms with moderate employee size, increase the economic pie, benefiting both employees and shareholders. The effects are weaker when there are too many employees to mitigate free‐riding. Although some large ESOPs increase productivity and employee compensation, the average impacts are small because they are often implemented for nonincentive purposes such as conserving cash by substituting wages with employee shares or forming a worker‐management alliance to thwart takeover bids.